Effects of Dietary Bopu Powder Supplementation on Serum Antioxidant Capacity, Egg Quality, and Intestinal Microbiota of Laying Hens - Liu, Hua; Lin, Qian; Liu, Xiubin; Huang, Peng; Yang, Zihui; Cao, Manhu; Liu, Mengting; Li, Xinyao; Zeng, Jianguo; He, Jianhua (Frontiers in Physiology, 2022)
The purpose of this study was to investigate the effects of dietary Bopu powder supplementation on the serum antioxidant capacity, serum biochemical indices, egg quality, and intestinal microbiota. Six hundred and forty-eight 33-week-old Lohmann Brown commercial laying hens were randomly allocated into six groups and fed a basal diet supplemented with 0, 25, 50, 100, 200, and 400 mg/kg Bopu powder for 8 weeks, denoted BP0, BP25, BP50, BP100, BP200, and BP400, respectively. The results showed that dietary Bopu powder supplementation reduced serum cholesterol concentrations (linear, p < 0.01) while increasing serum globulin and albumin concentrations (linear, p < 0.05). Furthermore, the BP50 and BP100 groups had greater serum catalase and glutathione peroxidase activity (p < 0.05). The egg Haugh Units were considerably higher in BP25 and BP50 (p < 0.05), and eggshell thickness was higher in BP25, BP200, and BP400 (p < 0.05) when compared to BP0. Dietary treatment with Bopu powder at doses ranging from 25–100 mg/kg improved glutathione peroxidase and catalase activities while decreasing malondialdehyde concentrations in the yolk (p < 0.05). The addition of Bopu powder increased the diversity of microbiota and the relative abundance of Bacteroidota in the gut. For instance, dietary Bopu powder supplementation of 25–50 mg/kg significantly raised the relative abundance of Enterococcus, Bacteroides, and Fusobacterium in the foregut. Supplementing the diet with 50–100 mg/kg of Bopu powder improved the relative abundance of Lactobacillus in the hindgut. In conclusion, dietary Bopu powder supplementation enhanced the abundance of beneficial bacteria in the foregut of laying hens and improved egg quality and antioxidant capacity. Furthermore, in the laying hen diet, the optimal dosage of Bopu powder additive was 25–50 mg/kg.